2019
DOI: 10.1111/cns.13260
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone ameliorates tissue plasminogen activator‐induced brain hemorrhage after stroke

Abstract: Objective Delayed thrombolytic therapy with recombinant tissue plasminogen activator (tPA) may exacerbate blood‐brain barrier (BBB) breakdown after ischemic stroke and lead to catastrophic hemorrhagic transformation (HT). Rosiglitazone(RSG), a widely used antidiabetic drug that activates peroxisome proliferator‐activated receptor‐γ (PPAR‐γ), has been shown to protect against cerebral ischemia through promoting poststroke microglial polarization toward the beneficial anti‐inflammatory phenotype. However, whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 48 publications
(98 reference statements)
0
32
0
Order By: Relevance
“…PPAR-γ agonists, including RSG also seem to reduce recurrent stroke and total related vascular events [24]. RSG treatment can minimize ischemic stroke through a variety of mechanisms, such as inhibiting in ammation, apoptosis and oxidative stress [25][26][27]. Studies have shown that RSG can increase the expression of caveolin-1 in cancer cells and macrophages [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-γ agonists, including RSG also seem to reduce recurrent stroke and total related vascular events [24]. RSG treatment can minimize ischemic stroke through a variety of mechanisms, such as inhibiting in ammation, apoptosis and oxidative stress [25][26][27]. Studies have shown that RSG can increase the expression of caveolin-1 in cancer cells and macrophages [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…(MMPs) (Mao et al, 2017). The integrity of BBB was further damaged after tPA treatment, which would eventually lead to lethal intracerebral hemorrhage (Li et al, 2019). Therefore, limiting inflammatory responses may help to reduce the risk of brain hemorrhage and improve the safety of tPA treatment following stroke.…”
Section: Discussionmentioning
confidence: 99%
“…RSG is a widely used antidiabetic drug which activates the PPAR-γ. RSG treatment can prevent ischemic stroke through a variety of mechanisms, such as inhibiting in ammation, apoptosis and oxidative stress [24][25][26]. Studies have shown that RSG can increase the expression of caveolin-1 in cancer cells and macrophages [27,28].…”
Section: Discussionmentioning
confidence: 99%